2011
DOI: 10.1007/s10620-011-1726-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter and G Protein Beta 3 Subunit Gene Polymorphisms in Greeks with Irritable Bowel Syndrome

Abstract: The results suggest that SERT and GNB3 gene polymorphisms might be associated with irritable bowel syndrome predisposition in Greeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…9,12,41,42 Only one Greek study showed significant association between T homozygotes (or T allele) and IBS. 43 In the present study, we could not find any significant association between this SNP and IBS, either. To our knowledge, as for the association between CCK1R intron 779T>C and IBS, only one study has been published.…”
Section: Discussioncontrasting
confidence: 77%
“…9,12,41,42 Only one Greek study showed significant association between T homozygotes (or T allele) and IBS. 43 In the present study, we could not find any significant association between this SNP and IBS, either. To our knowledge, as for the association between CCK1R intron 779T>C and IBS, only one study has been published.…”
Section: Discussioncontrasting
confidence: 77%
“…However, several additional studies found different results in other populations. A 2011 study in a Greek population found the GNβ3 -825T allele encoding a G protein that mediates enhances activation [11] to be closely associated with the occurrence of IBS [13]. A 2001 study conducted in a Caucasian population found that GNβ3 -825C was associated with increased defecation frequency [25], and Korean studies in 2010 and 2012 found GNβ3 -825T to be associated with IBS with constipation in adults [14] and children [16], and GNβ3 -825C to be associated with IBS with diarrhea in children [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, both Kim [12] and Saito [15] subdivided small populations (60 and 50 IBS patients, respectively) into CC, CT, and TT genotype subgroups, resulting in a smaller size in each group. The studies that found association between GNβ3 -C825T and IBS were conducted in ethnic Koreans [14] and Greeks [13]. Fang et al performed a correlation study between the GNβ3 C825T polymorphism and functional dyspepsia (FD) in a Han Chinese population, and found that this polymorphism is not a risk factor for the onset of FD [3].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Lee et al [87] showed that the T allele was associated with CIBS (Koreans; 12 CIBS, 51 DIBS, 31 MIBS; Rome III). Subsequently, T/T genotype and overall T allele frequencies of 825C>T were found to be associated with IBS in 124 Greek patients (Rome III) [88]. In the study by Kim et al [84], there was no association of 825C>T with susceptibility to IBS.…”
Section: G Proteinmentioning
confidence: 96%
“…rs5443 825C>T FD Association [13,45,79,80] FD Association (Hp-) [81] FD Association (EPS) [82] FD Association (PDS) [83] FD No association [84] IBS No association [51,74,[84][85][86] IBS Association (C-IBS) [80,87] IBS Association [88] IBS Association (D-IBS) [80] IBS Association (GI infection +) [89] Polymorphisms are reported as quoted in the original papers. When applicable, current designations, as reported in the NCBI SNP database Genetics & pharmacogenetics of aminergic transmitter pathways in functional gastrointestinal disorders Review intestinal fluid/electrolyte secretion, gastric and colonic tone and colorectal motility and sensation [90].…”
Section: Gnb3mentioning
confidence: 99%